Brief Communication: Economic Comparison of Opportunistic Infection Management With Antiretroviral Treatment in People Living With HIV/AIDS Presenting at an NGO Clinic in Bangalore, India - John, K.R. (Medscape, 2006)
CONTEXT: Highly active antiretroviral treatment (HAART) usage in India is escalating. With the government of India launching the free HAART rollout as part of the “3 by 5” initiative, many people living with HIV/AIDS (PLHA) have been able to gain access to HAART medications. Currently, the national HAART centers are located in a few district hospitals (in the high- and medium-prevalence states) and have very stringent criteria for enrolling PLHA. Patients who do not fit these criteria or patients who are too ill to undergo the prolonged wait at the government hospitals avail themselves of nongovernment organization (NGO) services in order to take HAART medications. In addition, the government program has not yet started providing second-line HAART (protease inhibitors). Hence, even with the free HAART rollout, NGOs with the expertise to provide HAART continue to look for funding opportunities and other innovative ways of making HAART available to PLHA. Currently, no study from Indian NGOs has compared the direct and indirect costs of solely managing opportunistic infections (OIs) vs HAART. OBJECTIVE: Compare direct medical costs (DMC) and nonmedical costs (NMC) with 2005 values accrued by the NGO and PLHA, respectively, for either HAART or exclusive OI management. STUDY DESIGN: Retrospective case study comparison. SETTING: Low-cost community care and support center – Freedom Foundation (NGO, Bangalore, south India). PATIENTS: Retrospective analysis data on PLHA accessing treatment at Freedom Foundation between January 1, 2003 and January 1, 2005. The HAART arm included case records of PLHA who initiated HAART at the center, had frequent follow-up, and were between 18 and 55 years of age. The OI arm included records of PLHA who were also frequently followed up, who were in the same age range, who had CD4+ cell counts < 200/microliter (mcL) or an AIDS-defining illness, and who were not on HAART (solely for socioeconomic reasons). A total of 50 records were analyzed. Expenditures on medication, hospitalization, diagnostics, and NMC (such as food and travel for a caregiver) were calculated for each group. RESULTS: At 2005 costs, the median DMC plus NMC in the OI group was 21,335 Indian rupees (Rs) (mean Rs 24,277/-) per patient per year (pppy) (US $474). In the HAART group, the median DMC plus NMC was Rs 18,976/- (mean Rs 21,416/-) pppy (US $421). Median DMC plus NMC pppy in the OI arm was Rs 13623.7/- paid by NGO and Rs 1155/- paid by PLHA. Median DMC and NMC pppy in the HAART arm were Rs 1425/- paid by NGO and Rs 17,606/- paid by PLHA. CONCLUSIONS: Good health at no increased expenditure justifies providing PLHA with HAART even in NGO settings.